Evaluation Effect of Aspiration of 0.2 ml of Cerebrospinal Fluid After Completion of Injection 0.5% Bupivacaine and Reinjection Into Subarachnoid Space on Sensory and Motor Block in Cesarean Section: A Randomized Clinical Trial - Manouchehrian, Nahid; Miri, Zahra; Esna-Ashari, Farzaneh; Rahimi-Bashar, Farshid (Frontiers in Medicine, 2022)
Background: Spinal anesthesia (SPA) is the most common type of anesthesia administered for caesarean section. The main aim of this study was to evaluate the effect of aspiration of CSF (0.2 mL) immediately after SPA with hyperbaric 0.5% bupivacaine on the extent of sensory and motor block. Methods: In this clinical trial, 60 women at ≥37 weeks of gestation and aged between 18-46 years, candidate for cesarean delivery under spinal anesthesia were randomly allocated into two equal groups (n=30). Group A (CSF-aspiration group) received the spinal anesthesia with 10 mg of hyperbaric 0.5% bupivacaine with aspiration of 0.2 ml of CSF. Group B (no-CSF-aspiration group) received only 10 mg of 0.5% hyperbaric bupivacaine. Pin-prick analgesia and motor block were tested during the induction. Results: The mean maximum level of analgesia was T6 in each group. Although the mean time to reach the maximum level of anesthesia (4.43±5.14 vs.2.76±2.04, P=0.107) and to reach T10 level (50.56±11.51 vs. 49.10±13.68, P=0.665) in the CSF-aspiration group is longer than the non-CSF-aspiration group, but this differences were not significant. There were no significant between-group differences regarding sensory and motor block quality (P=0.389) or failed SPA (4 cases in CSF-aspiration group vs. 2 cases in no-CSF-aspiration group, P=0.389). The incidence of bradycardia, hypotension, headache, vomiting and nausea were similar in both groups (P>0.05). In addition, the difference in hemodynamic parameters between the two groups over times was not statistically significant. Conclusion: Our finding indicated that the aspiration of 0.2 ml of CSF after injection of spinal anesthesia with hyperbaric 0.5% bupivacaine does not seem to affect the extent of sensory and motor block, success rate, or outcome after SPA in cesarean section. Clinical trial registration: URL: https://www.irct.ir/search/result?query=IRCT20120915010841N25, Identifier: IRCT20120915010841N25